A/D-rings-seco limonoids from the fruits of Aglaia edulis and their bioactivities. (March 2022) - Sun, Yujin; Cui, Letian; Sun, Yunpeng; Li, Qiurong; Li, Yongyi; Wang, Zefan; Xu, Wenjun; Kong, Lingyi; Luo, Jun
Abstract: Agledulines A-K, eleven previously undescribed limonoids, including eight biogenic A/D-rings- seco limonoid analogs (agledulines A-H), one D-ring- seco limonoid (agleduline I) and two A-ring- seco limonoids with a rare Δ 4, 28 moiety (agledulines J-K), together with twelve reported limonoids, were isolated from the fruits of Aglaia edulis . Their structures were determined by NMR data, HRESIMS, X-ray diffraction, ECD spectra and the CD exciton chirality method. Observably, the absolute configurations of agleduline A, agleduline C and nymania 2 were unambiguously elucidated by single-crystal X-ray diffraction analyses. The biological evaluation showed that agleduline C exhibited significant cytotoxic activities with IC50 values of 10.05 μ M, and 11 α -acetoxygedunin showed notable anti-inflammatory activity (IC50 : 4.70 μ M). In addition, agleduline I and 11 α -acetoxygedunin reversed the multidrug resistance with IC50 values of 5.05 and 1.49 μ M (RI: 4.64 and 15.77) in the MCF-7/Dox cells. Graphical abstract: Image 1 Highlights: Eleven previously undescribed limonoids were isolated from the Aglaia edulis. Their absolute configurations were elucidated by X-ray crystallography and ECD. Eight limonoids exhibited diverse bioactivities.